Operando electrochemical NMR microscopy of polymer fuel cells1. Issue 8 (29th August 2015) - Cattaneo, A. S.; Villa, D. C.; Angioni, S.; Ferrara, C.; Melzi, R.; Quartarone, E.; Mustarelli, P.
<x xml:space="preserve">Abstract</x> Electrochemical NMR microscopy is a breakthrough in operando characterization of electrochemical devices, such as fuel cells and batteries.